Immunotherapy and delivery systems for melanoma - Hui Liu; Xi Gou; Yuanfang Tan; Qiuying Fan; Juanjuan Chen (Human Vaccines & Immunotherapeutics)
Melanoma is a highly malignant tumor of melanocyte origin that is prone to early metastasis and has a very poor prognosis. Early melanoma treatment modalities are mainly surgical, and treatment strategies for advanced or metastatic melanoma contain chemotherapy, radiotherapy, targeted therapy and immunotherapy. The efficacy of chemotherapy and radiotherapy has been unsatisfactory due to low sensitivity and strong toxic side effects. And targeted therapy is prone to drug resistance, so its clinical application is limited. Melanoma has always been the leader of immunotherapy for solid tumors, and how to maximize the role of immunotherapy and how to implement immunotherapy more accurately are still urgent to be explored. This review summarizes the common immunotherapies and applications for melanoma, illustrates the current research status of melanoma immunotherapy delivery systems, and discusses the advantages and disadvantages of each delivery system and its prospects for clinical application.